A Case of a 5-Year-Old Boy with a Blauth Type IIIB Hypoplastic Thumb Reconstructed with a Nonvascularized, Hemilongitudinal Metatarsal Transfer - Mika Nakada; Kaoru Tada; Tadahiro Nakajima; Masashi Matsuta; Hiroyuki Tsuchiya (Case Reports in Orthopedics)
The treatment methods used for Blauth type IIIB hypoplastic thumbs are controversial. We performed a nonvascularized, hemilongitudinal metatarsal bone transfer on a 5-year-old boy with a type IIIB hypoplastic thumb. Despite the child’s age, the growth of the thumb was confirmed and the thumb had stabilized. Moreover, growth disorder of the donor toe was not observed. This method is relatively easy to perform. And donor toe deformation can be prevented, because of the preservation of more than half of the metatarsal bone. In our case, the patient was 5 years of age; nevertheless, the epiphyseal line was opened and the grafted metatarsal bone grew. This method is useful in terms of its simplicity and prevention of postoperative complications.